Penerapan Metode WASPAS dalam Pemilihan Handphone Gaming Terbaik - Sitti Nur Alam; Hendrikus Haipon; Septiana Ningtyas; Saludin Saludin; Kraugusteeliana Kraugusteeliana (Journal of Computer System and Informatics (JoSYC), 2023)
The technology that people are most interested in is mobile phones. Apart from being a tool for exchanging information and as a means of communication, mobile phones are also used as entertainment tools such as playing games. The large number of HP brands confuses potential buyers in determining which HP brand is good. To help the public in choosing the best HP Gaming brand, this can be done by using the SPK. SPK is a system where the procedure for working is to use a computer working procedure. In using SPK, must use the method. In this study the method used was the WASPAS method. The WASPAS method is a method that uses 2 steps, where the first step is to calculate normalization by carrying out the division operation. By implementing the WASPAS method, a value of 2.9710 is obtained as an alternative to A2 as the best HP Gaming brand with the Infix Zero 20 brand.